Sustainable Architecture in Egypt: A Historical Analysis - Sara Alansary; Dalia Abdelfattah (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The growth of what we may, in the present context, describe as "unsustainable architecture" began with the industrial revolution, as more and more new technologies were incorporated into the fabric of buildings. Before all these developments most buildings employed the properties of material and form to provide appropriate relationships between their uses and the environments. In other words, Buildings of the past were sustainable. This paper will present the background of Sustainable Architecture features in Egypt by studying ancient  Egyptian architecture to address sustainability features through architecture heritage with focus on the ancient civilization and Islamic civilization in Egypt. The research methodology encompasses the establishment of criteria for evaluating sustainability of architectural products, followed by a comprehensive review of these products during periods under study. Furthermore, the historical approaches towards sustainable architecture examined allows the formulation of recommendations aimed at enhancing contemporary Egyptian architecture.